Western Balkans trade to European Union - Popovici Alexandra (2021)
European Union trade with the Western Balkans shows considerable room for growth in both imports and exports. The primary purpose of this thesis is to assess the potential impact of the trade relationships of Western Balkans-6 and Europeans Union over Economy of Republic of Albania, Bosnia and Herzegovina, Montenegro, Kosovo, Republic of North Macedonia, and Serbia. As well as to evaluate where countries and economies in the Western Balkan region stand with respect to the three fundamentals for the EU-enlargement process. The thesis discusses the structural changes in bilateral trade flows between Western Balkan countries. The basic idea was to address whether there is a justification for the often-proposed deepening of economic cooperation among Western Balkan states. This thesis presents an overview of key studies related to Western Balkans and European Union trade relations and how it impacts different sectors of society. The overview clearly indicates quite large support for views underlining the benefits and challenges in relations between countries in the regions, as well as with European Union member states particularly. In addition, this research through comparative statistical evidence observes the convergence of the Western Balkans economies with the EU and further considers catching-up with the EU living standard. This assumes increasing competitiveness through higher investments and credible structural reforms, which also requires credible policymaking and political leadership. First chapter is introducing in the topic, providing key concepts and recent research results related to international trade. Furthermore, this chapter includes an overview of Western Balkan countries economies and latest trends in their economic development in the last years. Delving into the history of the relationship between European Union and Western Balkans, chapter two investigates relationships between the European Union and Western Balkans in different periods time. Results of intra-regional cooperation analyses, helps to identify individual challenges of European Enlargement process. Based on these theoretical and empirical findings such as: openness of those economies to world markets, their main partners by export and import volume, the structure of exports and imports by group classification of commodities, in Chapter two and three are made analysis of the structure and dynamics of exports and imports according to each country in the Western Balkans.